2021
DOI: 10.1093/ehjqcco/qcab068
|View full text |Cite
|
Sign up to set email alerts
|

The PRECISE-DAPT score and 5-year outcomes after percutaneous coronary intervention: a large-scale, real-world study from China

Abstract: Aims The PRECISE-DAPT score is recommended by guidelines for predicting out-of-hospital bleeding in patients after percutaneous coronary intervention (PCI). However, the long-term prognostic value of the PRECISE-DAPT score in patients after PCI remains unclear. Methods and Results We performed a prospective study of 10,724 patients who underwent PCI throughout 2013 in Fuwai hospital. The bleeding endpoint was Bleeding Academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…29 It should be interpreted in light of the reduced frequencies of age≥75 years (8.3% versus 38.0%), long-term use of oral anticoagulation (0.7% versus 8.7%), moderate or severe anemia (12.3% versus 50.2%), malignancy (2.4% versus 8.7%), chronic kidney disease (18.0% versus 34.2%; severe/end-stage chronic kidney disease: 0.2% versus 11.0%), and transfemoral access (24.4% versus 92.6%) in our study compared with those in the Mount Sinai registry. Although HBR rate would seem low, our results were in keeping with prior findings validating the ARC-HBR definition 30,31 (XIENCE V China registry: <22.0%; I-LOVE-IT 2 trial: 16.0%) and PRECISE-DAPT score 32,33 (2 observational registries: 4.4% and 9.7%) in China. Another reason for the discrepancy in safety of prolonged DAPT could be that clopidogrel was the predominant P2Y 12 inhibitor in the patients in the study, whereas only 8% of patients were treated with ticagrelor plus aspirin at discharge.…”
Section: Discussionsupporting
confidence: 91%
“…29 It should be interpreted in light of the reduced frequencies of age≥75 years (8.3% versus 38.0%), long-term use of oral anticoagulation (0.7% versus 8.7%), moderate or severe anemia (12.3% versus 50.2%), malignancy (2.4% versus 8.7%), chronic kidney disease (18.0% versus 34.2%; severe/end-stage chronic kidney disease: 0.2% versus 11.0%), and transfemoral access (24.4% versus 92.6%) in our study compared with those in the Mount Sinai registry. Although HBR rate would seem low, our results were in keeping with prior findings validating the ARC-HBR definition 30,31 (XIENCE V China registry: <22.0%; I-LOVE-IT 2 trial: 16.0%) and PRECISE-DAPT score 32,33 (2 observational registries: 4.4% and 9.7%) in China. Another reason for the discrepancy in safety of prolonged DAPT could be that clopidogrel was the predominant P2Y 12 inhibitor in the patients in the study, whereas only 8% of patients were treated with ticagrelor plus aspirin at discharge.…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that PRECISE-DAPT score had a predictive value for 5-year bleeding, mortality, and MACCE. 11 Similarly, this score was predictive of both bleeding and MACCE in the present study. Also, a high score was an independent predictor of all-cause mortality at long-term follow-up in our study.…”
Section: Discussionsupporting
confidence: 76%
“…10 There are limited data showing the association of PRECISE-DAPT scores with long-term mortality. 11 In our study, we aimed to evaluate the value of this scoring in terms of major bleeding, cardiovascular outcomes, and mortality during long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…As researchers realize the core importance of balancing between ischemic and bleeding risks in APT, more studies are addressing patients who fall into the "high bleeding risk" (HBR) category. Tools such as the PRECISE-DAPT score [59] (>25 points) and Academic Research Consortium for High Bleeding Risk (ARC-HBR) criteria [60] (one major or two minor criteria) have also been developed for identifying HBR patients.…”
Section: Hbr Patientsmentioning
confidence: 99%
“…The DAPT score successfully stratified ischemic and bleeding risks in a pooled cohort of 12,223 Japanese patients [77]; however, the authors noted that ischemic event rates were low, even in patients with high DAPT scores. To evaluate bleeding risks, the PRECISE-DAPT score provides a standardized tool to predict out-of-hospital bleeding and has been validated in both Chinese and Korean populations [59,78]. Developed from the records of 32,057 patients from Hong Kong, the CARDIAC score [79] helps to predict the risk of major bleeding within 1 year after PCI, based on anticoagulation therapy, age, renal insufficiency, drop in hemoglobin levels, and baseline anemia.…”
Section: Risk Assessment In Asian Patientsmentioning
confidence: 99%